Ancient past, imperial present : the British Empire in T.J. Dunbabin's The western Greeks - De Angelis, Franco
T.J. Dunbabin's book The western Greeks was published 50 years ago. In it he modelled the development of the Greek cities of Italy on the British Empire of the 1930s. Here Franco De Angelis explores the problem of faulty and distorting analogies.